A Super‐Formula‐based compact ultra‐wideband antenna and its application to indoor real‐time positioning systems. Issue 11 (18th July 2022) - Yang, Kansheng; Song, Zhe; Gielis, Johan; Caratelli, Diego
Abstract: A Super‐Formula‐based compact ultra‐wideband (UWB) printed monopole antenna is proposed in this paper. The presented design is implemented by using inexpensive FR‐4 laminates, and is optimized so as to enable excellent radio frequency performance in terms of impedance matching, realized gain, total efficiency, radiation pattern characteristics, maximal group delay variation, and system fidelity factor (SFF), while covering the Federal Communications Commission UWB channel 5, from 6.24 to 6.74 GHz, and channel 9, from 7.74 to 8.24 GHz. The proposed antenna solution has been characterized both passively and actively using a commercially available indoor real‐time positioning system, which relies on the phase‐difference‐of‐arrival algorithm. The collected measurement results demonstrate the high accuracy in real‐time positioning achieved with the developed antenna both in terms of distance and angle.